Dietary supplementation of 3′-sialyllactose or 6′-sialyllactose elicits minimal influence on cognitive and brain development in growing pigs - Golden, Rebecca K.; Sutkus, Loretta T.; Donovan, Sharon M.; Dilger, Ryan N. (Frontiers in Behavioral Neuroscience, 2024)
Sialylated human milk oligosaccharides (HMO), such as 3ˊ-sialyllactose (3ˊ-SL) and 6ˊsialyllactose (6ˊ-SL), are abundant throughout lactation and at much higher concentrations than are present in bovine milk or infant formulas. Previous studies have suggested that sialylated HMO may have neurocognitive benefits in early life. Recent research has focused on infant formula supplementation with key nutrients and bioactives to narrow the developmental gap between formula-fed and breastfed infants. Herein, we investigated the impact of supplemental 3ˊ-SL or 6ˊ-SL on cognitive and brain development at two time-points [postnatal days (PND) 33 and 61]. Two-day-old piglets (N = 75) were randomly assigned to commercial milk replacer ad libitum without or with 3ˊ-SL or 6ˊ-SL (added in a powdered form at a rate of 0.2673% on an asis weight basis). Cognitive development was assessed via novel object recognition and results were not significant at both time-points (P > 0.05). Magnetic resonance imaging was used to assess structural brain development. Results varied between scan type, diet, and time-point. A main effect of diet was observed for absolute volume of white matter and 9 other regions of interest (ROI), as well as for relative volume of the pons on PND 30 (P < 0.05). Similar effects were observed on PND 58. Diffusion tensor imaging indicated minimal differences on PND 30 (P > 0.05). However, several dietary differences across the diffusion outcomes were observed on